Investigation of radiation damage using thermal spike model for SHI irradiation on Al2O3. Issue 5 (3rd June 2022) - Patra, Paramita; Shah, Sejal; Toulemonde, M.; Sulania, I.; Singh, F.
Abstract : The material exposed to energetic radiation may change its properties and performance. Ion beam irradiation is an established method to investigate radiation damage in materials. In the present study, SRIM code is employed as a tool to determine the electronic and nuclear energy losses and displacement per atom (DPA) associated with the damage induced in Al2 O3 using 100 MeV Au ion. We have further studied the creation of 100 MeV Au ion induced molten zone along the ion track in Al2 O3 in the framework of the thermal spike (TS) model. Using the in-elastic thermal spike model, elastic thermal spike model, and unified thermal spike model, the evolution of lattice temperature and latent track radius as a function of depth of Al2 O3 for 100 MeV Au ion irradiation are investigated. The current results demonstrate that the latent track radius shows a U-shaped variation based on the combined effect of electronic stopping power and nuclear stopping power. In order to corroborate these results, an additional irradiation experiment was performed using swift heavy ion (SHI), 100 MeV Au ions with fluence 1×10 14  ions/cm 2 for Al2 O3 . To investigate the structural properties, surface morphology and to identify the defects in the samples, pristine and irradiated Al2 O3 samples were characterized by Grazing Incident X-Ray Diffraction (GIXRD), Atomic Force Microscopy (AFM) and Photoluminescence Spectroscopy (PL). AFM study shows the increase in roughness after SHI irradiation. A decrease in intensity of PL spectra upon SHI irradiation indicates the formation of new defects and disordered structures in the material, which is quite in agreement with the theoretical results.